Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. The impact of information technology on human resource management practices from the perspective of education administration employees in JeddahMs. Arwa Mohamad Alharbi, Ms. Henda Salem Matoussi2. The Impact of Accounting Information Systems’ Characteristics on Organizational Performance by Using Leadership Style: A Field Study on Saudi Industrial CorporateMrs. Shahad Ahmed Alaseeri, Co-Prof. Rawia Reda Obaid3. Water problem and its implications for sustainable developmentWael Mohammed Al-Malki, Saleh Ibrahim Al-Shamsan, Abdulmalek Faisal Al-Alewi, Mansour Abdullah Al-Shebil, Issam Suleiman Al-Naser4. An econometric study of the Phillips curve with inflationary expectations in the Saudi economy  for the period 1997-2022Dr. Emad Adnan Matyori5. The Assumption of the Judiciary in Palestinian Territories: Balancing Islamic Law and Secular LawMr. Gaber Mohammed Alorgan6. The Impact of Strategic Planning on Key Performance Indicators in the Saudi Private Sector  in Light of Saudi Vision 2030Dr. Arwa Mohammed Alawwad7. Forensic accounting and its role in reducing financial corruptionA field study applied on some judicial institutions in the Kingdom of Saudi ArabiaDr. Mohammed Elsadig Abdallah
Keywords: Journal of Economic, Administrative and Legal Sciences